2021
DOI: 10.1037/amp0000818
|View full text |Cite
|
Sign up to set email alerts
|

The new science of religious change.

Abstract: Humans have believed in gods and spirits since the earliest days of the Holocene, and many people still believe in them today. Although the existence of religious belief has been a human constant, the nature and prevalence of religion has changed dramatically throughout human history. Here we describe the emerging science of religious change. We first outline a multilevel framework for studying religious change drawn from theories of socioecological psychology and cultural evolution. We illustrate this framewo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 80 publications
(104 reference statements)
0
17
0
1
Order By: Relevance
“…Agama dan sains tidak berseberangan dalam merespon situasi yang terjadi selama pandemi COVID-19 di Indonesia, dan keduanya memiliki porsi masing-masing dalam memberikan penjelasan atas permasalahan yang terjadi. Jackson et al (2021) menemukan bahwa agama tidak selamanya menghambat individu dalam menerima sains yang ada. Namun, sejumlah individu yang non-religius kerap memiliki prasangka tersebut.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Agama dan sains tidak berseberangan dalam merespon situasi yang terjadi selama pandemi COVID-19 di Indonesia, dan keduanya memiliki porsi masing-masing dalam memberikan penjelasan atas permasalahan yang terjadi. Jackson et al (2021) menemukan bahwa agama tidak selamanya menghambat individu dalam menerima sains yang ada. Namun, sejumlah individu yang non-religius kerap memiliki prasangka tersebut.…”
Section: Discussionunclassified
“…Religion and science are not completely in opposite corners in responding to the situation which is occuring during the COVID-19 pandemic in Indonesia, and each of them has its own place in explaining the problems which have occurred. Jackson et al (2021) found that religion does not always hinder people in accepting the existing science. Nonetheless, a number of non-religious people often have that preconception.…”
Section: Apakah Agama Dan Sains Dapatmentioning
confidence: 99%
“…Finally, this special issue aims to make methods in cultural dynamics research feel more approachable to those who may be less familiar with them. This issue contains accessible overviews of agent-based modeling (Schaller & Muthukrishna, 2021) and broad discussions of common time series methods (Jackson et al, 2021; Rotella et al, 2021; also see https://osf.io/njydv/ for annotated R code for many common time series analyses). Further, several articles identify additional overviews and tutorials for those interested in becoming more familiar with these and other methods highlighted in this issue that are not typically part of the psychologist’s statistical toolkit.…”
Section: Improving Accessibilitymentioning
confidence: 99%
“…Some of the articles in this special issue focus on the "What" of cultural change-documenting shifts in specific phenomena such as prejudice (Charlesworth & Banaji, 2021), mental health (Infurna et al, 2021), individualism (Hamamura et al, 2021), social mobility (Chan et al, 2021), and religious beliefs and practices (Jackson et al, 2021). Other articles focus on the "Why"-testing theories regarding the causes of specific cultural changes, such as shifts over time in levels of individualism (Kusano & Kemmelmeier, 2021), or openness (Götz et al, 2021), or fertility (Rotella et al, 2021).…”
mentioning
confidence: 99%
See 1 more Smart Citation